High-temperature continuous-wave laser realized in hollow microcavities - Shi, Zhifeng (Nature Publishing Group, 2014)
Recently, an urgent requirement of ultraviolet (UV) semiconductor laser with lower cost and higher performance has motivated our intensive research in zinc oxide (ZnO) material owing to its wide direct band gap and large exciton binding energy. Here, we demonstrate for the first time continuous-wave laser in electrically-pumped hollow polygonal microcavities based on epitaxial ZnO/MgO-core/shell nanowall networks structures, and whispering gallery type resonant modes are responsible for the lasing action. The laser diodes exhibit an ultralow threshold current density (0.27 A/cm2), two or three orders of magnitude smaller than other reported UV-light semiconductor laser diodes to our knowledge. More importantly, the continuous-current-driven diode can achieve lasing up to ~430 K, showing a good temperature tolerance. This study indicates that nano-size injection lasers can be made from epitaxial semiconductor microcavities, which is a considerable advance towards the realization of practical UV coherent light sources, facilitating the existing applications and suggesting new potentials.